1994
DOI: 10.1007/bf00235493
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte structure in dominant and subordinate follicles in zebu cattle (Bos indicus)

Abstract: The objective of the study was to investigate the light and ultrastructural morphology of dominant and subordinate oocytes from zebu (Bos indicus) cattle. Healthy cycling animals, which had a well-developed corpus luteum as judged by rectal palpation, were administered cloprostenol to induce luteolysis and therefore ovulation. The animals were slaughtered at days 3-11 post-ovulation, but those slaughtered at days 8-11 received a second injection of cloprostenol at day 7. Cumulus-oocyte complexes were aspirated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
5
14
0
1
Order By: Relevance
“…This can be explained by the formation of the zona pellucida that blocks the close contact between oocyte and granulosa cells. Coated pits are commonly observed in early preantral follicles of cattle (Fair et al, 1997a andHyttel et al, 1997) and other species (Lucci et al, 2001), while gap junctions are more commonly observed in more developed follicles, especially after the development of the zona pellucida (Assey et al, 1994a, Fair et al, 1997aand Hyttel et al, 1997.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the formation of the zona pellucida that blocks the close contact between oocyte and granulosa cells. Coated pits are commonly observed in early preantral follicles of cattle (Fair et al, 1997a andHyttel et al, 1997) and other species (Lucci et al, 2001), while gap junctions are more commonly observed in more developed follicles, especially after the development of the zona pellucida (Assey et al, 1994a, Fair et al, 1997aand Hyttel et al, 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made in developing the reproductive technologies for zebu cattle, especially because these animals are economically important to Brazil. However, very few studies have been developed to describe the morphology of ovarian follicles in B. indicus ( Assey et al, 1994a andBasso andEsper, 2002). The present work aimed, therefore, to morphologically characterize ovarian preantral follicles from zebu cattle (B.…”
Section: Introductionmentioning
confidence: 99%
“…However, TEM revealed that follicles cryopreserved in 1.5 M EG had many signs of ultrastructural abnormality, such as the presence of numerous vacuoles in the oocyte cytoplasm. Hay et al [45] and Assey et al [46] demonstrated that cytoplasmic vacuoles are also a characteristic sign of degeneration in both granulosa and cumulus cells during degeneration in vivo. According to Fuku et al [47], in bovine cryopreserved oocytes, these vacuoles may represent altered mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Tassel and Kennedy (1980) and van den Hurk et al (1998) emphasized that oocytes showing signs of atresia in vivo contain numerous vacuoles. The cytoplasmic vacuoles are also a characteristic sign of degeneration in granulosa (Hay et al, 1976) and cumulus cells (Assey et al, 1994) during degeneration in vivo and may represent endoplasmic reticulum swelling. Conversely, these vacuoles may represent altered mitochondria, as observed in cryopreserved bovine oocytes by Fuku et al (1995).…”
Section: Discussionmentioning
confidence: 99%